Thermal energy storage and mechanical enhancement of cement composites containing PCM-impregnated and cement-slurry coated pumice aggregates - Gençel, Osman; Ozguler, Alper Tunga; Guler, Onur; Ustaoğlu, Abid; Hekimoglu, Gokhan; Sari, Ahmet; Emiroglu, Mehmet; Gençel, Osman; Ustaoğlu, Abid (Elsevier, 2025)
In the field of thermal energy management and building materials, PCM has been impregnated into aggregates and added to cement to produce composite concretes. However, challenges such as PCM leakage and poor interfacial bonding have limited their widespread application. To address these issues, this study utilized pumice aggregates with exceptional porosity, impregnated with PCM and coated with cement slurry, to develop enhanced composite concretes. The produced composites were characterized through compressive strength tests, thermal conductivity measurements, ultrasonic pulse velocity analysis, and detailed thermal regulation experiments under dynamic solar radiation. Thermal regulation experiments were conducted using thermal imaging under real-time heating and cooling processes. Results demonstrated that PCM-impregnated aggregates enhanced the thermal stability of concrete, with surface temperatures on PCM-based composites (MAL-2) being approximately 5 degrees C lower during heating compared to control samples (MAL-K). During the cooling process, MAL-2 exhibited delayed temperature reduction, stabilizing surface temperatures around 1 degrees C higher than MAL-K due to PCM's latent heat release. Experimental outcomes further presented that an increasing proportion of PCM-impregnated aggregates significantly reduced porosity from 13.55 % to 7.87 % and improved compressive strength from 12.7 MPa to 16.81 MPa. Thermal conductivity increased from 0.5706 to 0.7058 W/mK, while water absorption decreased from 13.94 % to 7.13 %. Ultrasonic pulse velocity values increased from 2.49 km/s to 2.58 km/s, indicating enhanced matrix integrity. This design, offering superior thermal regulation and mechanical performance, holds great promise for applications in energy-efficient building materials and sustainable construction practices.
Keywords: Coated Pumice Aggregate; Phase Change Material; Sustainable Concrete; Energy And Energy Efficiency; Renewable Energy; Surface Modification